Defoe's footprints : essays in honour of Maximillian E. Novak - Maniquis, Robert M.; Fisher, Carl, 1958-; Novak, Maximillian E. (UCLA Clark Memorial Library series, 2009)
With attention to Defoe's neglected writings as well as to his important works, this volume uncovers his distance from and influence on modern literature, paying tribute to Maximillian E. Novak by presenting new ideas about, and new readings of, Daniel Defoe.